2020
DOI: 10.1016/j.jbusres.2019.04.015
|View full text |Cite
|
Sign up to set email alerts
|

R&D innovation indicator and its effects on the market. An empirical assessment from a financial perspective

Abstract: We propose an alternative firm-level measure for innovation activities-R&D elasticity-and we analyse its effects on the Tobin's Q of listed companies on the Euronext 100 Index. We find that R&D elasticity is positively related to market appreciation by stakeholder investors. Moreover, we analyse the role of default risk in the relationship between innovation activities and market value, and find that firms' default probabilities are negatively related to Tobin's Q. These findings are supported by OLS regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 148 publications
(154 reference statements)
8
56
3
Order By: Relevance
“…This is also different from the conclusions of existing research. Previous studies on innovation and social responsibility have only concluded that these two factors have a substitution effect on each other [6,7]. However, this study found that green innovation only has a substitution effect on social information disclosure, and this effect gradually decreases with the increase of firm value.…”
Section: Test Of the Interactive Impact Of Green Innovation And Esg Icontrasting
confidence: 57%
See 4 more Smart Citations
“…This is also different from the conclusions of existing research. Previous studies on innovation and social responsibility have only concluded that these two factors have a substitution effect on each other [6,7]. However, this study found that green innovation only has a substitution effect on social information disclosure, and this effect gradually decreases with the increase of firm value.…”
Section: Test Of the Interactive Impact Of Green Innovation And Esg Icontrasting
confidence: 57%
“…Similarly, Coluccia et al (2019) found that there is a substitution effect occurring between investment in R&D and ESG scores. Investment in R&D can improve enterprise performance, while the ESG score has no significant impact on enterprise performance, so enterprises should disclose a greater amount of relevant R&D information to stakeholders [6].…”
Section: Interaction Effect Of Green Innovation and Esg On Firm Valuementioning
confidence: 89%
See 3 more Smart Citations